1)Simplify;

2x^2-y^2+xy/x^2-y^2

3 answers

To simplify the expression, we can first factor the numerator and denominator separately.

For the numerator, we observe that there is a common factor of xy:
2x^2 - y^2 + xy = xy(2x - y)

For the denominator, we can apply the difference of squares formula:
x^2 - y^2 = (x - y)(x + y)

Now, we can simplify the expression:
(2x^2 - y^2 + xy)/(x^2 - y^2) = (xy(2x - y))/((x - y)(x + y))

The final simplified expression is: (xy(2x - y))/((x - y)(x + y))
This step is wrong.
2x^2 - y^2 + xy = xy(2x - y)
There is no common factor of xy.

Instead,
(2x^2-y^2+xy)/(x^2-y^2) = (2x+y)(x-y) / (x+y)(x-y) = (2x+y)/(x+y)
Apologies for the mistake in the previous step.

The correct simplification is:
(2x^2 - y^2 + xy)/(x^2 - y^2) = (2x + y)/(x + y)